Thalassiobeckiaceae – a new family of the class Centrophyceae (Bacillariophyta) - Khursevich, G.K.; Fedenya, S.A. (Альгология, 2005)
A new freshwater genus Thalassiobeckia studied in light (LM) and scanning electron microscope (SEM) from the Pliocene sediments of Lake Baikal has been considered in the composition of the new monotype family Thalassiobeckiaceae in the class Centrophyceae (Bacillariophyta). Both new taxa are diagnosed by a combination of following morphological features: a) the presence of loculate areolae with internal cribra and external foramina; b) the arrangement of areolae on the valve face in radiating non-fasciculated striae; c) the presence of the marginal ring of tubular processes on the valve mantle; d) the availability of several rimoportulae on the valve face/mantle junction and e) the availability of one-several valve face fultoportula. Новый пресноводный род Thalassiobeckia, изученный в световом (СМ) и сканирующем электронном микроскопе (СЭМ) из плиоценовых отложений озера Байкал, рассматривается в составе нового монотипного семейства Thalassiobeckiaceae в классе Centrophyceae (Васillariophyta). Оба новых таксона характеризуются сочетанием следующих морфологических признаков: а) присутствием локулярных ареол с внутренним крибрумом и наружным фораменом; b) расположением ареол и лицевой поверхности створки в радиальных рядах, не образующих пучки; c) присутствием краевого кольца трубковидных выростов на загибе створки; d) наличием нескольких двугубых выростов на границе лицевой части створки и загиба и (е) одного-нескольких выростов с опорами на лицевой части створки.